Effect of demonstration-method counseling on the understanding of correct breastfeeding techniques among pregnant women - Fatmawati; Meldawati; Palimbo, Adriana; Mahdiyah, Dede (Health Sciences International Journal, 2024)
Background: Exclusive breast milk is food with nutritional content most suitable for the baby's needs, protects against various infections, and provides a loving relationship that supports all aspects of the baby's development, including the baby's health and intelligence. The success of breastfeeding depends on the understanding of the breastfeeding technique used by the mother. Objective: Analyzed the effect of demonstration-method counseling on understanding correct breastfeeding techniques among pregnant women. Method: The research used a quasi-experimental design with pre- and post-tests. Based on established criteria, 55 samples were taken purposively from 133 pregnant women who underwent examinations at the Muara Koman Community Health Center. Demographic data and pregnant women's understanding of breastfeeding techniques were collected using questionnaires. Analysis was carried out using SPSS. Results: Counseling with demonstration methods for pregnant women can increase understanding of correct breastfeeding techniques. This is shown in the pretest results before being given demonstration method counseling with a score of 30 (52.6%), increasing to a score of 51 (89.5%). Comparative analysis of the pre-and post-tests showed a significant effect of counseling using the demonstration method on the level of understanding of pregnant women about correct breastfeeding techniques with a p-value <0.05. Conclusion: Counseling with a suitable demonstration method is provided to increase pregnant women's understanding of breastfeeding correctly.